2018
DOI: 10.1136/gutjnl-2018-316906
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction proteins in gastrointestinal and liver disease

Abstract: Over the past two decades a growing body of evidence has demonstrated an important role of tight junction (TJ) proteins in the physiology and disease biology of GI and liver disease. On one side, TJ proteins exert their functional role as integral proteins of TJs in forming barriers in the gut and the liver. Furthermore, TJ proteins can also be expressed outside TJs where they play important functional roles in signalling, trafficking and regulation of gene expression. A hallmark of TJ proteins in disease biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
185
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(191 citation statements)
references
References 247 publications
4
185
0
2
Order By: Relevance
“…Separating epithelial cells are various junctions, including tight junction (TJ), adherence junction, and gap junction . Among which, TJ plays a crucial role in maintaining the intestinal epithelial barrier integrity . The dysfunction of TJ increases the paracellular permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separating epithelial cells are various junctions, including tight junction (TJ), adherence junction, and gap junction . Among which, TJ plays a crucial role in maintaining the intestinal epithelial barrier integrity . The dysfunction of TJ increases the paracellular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…35 Among which, TJ plays a crucial role in maintaining the intestinal epithelial barrier integrity. 36,37 The dysfunction of TJ increases the paracellular permeability. The entry of luminal pro-inflammatory molecules induces mucosal immune system activation, resulting in sustained inflammation and tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of epithelial barrier integrity in EoE is attributed to the downregulation of important structural proteins in the inflamed mucosa including tight junction (TJ) proteins . The tight junction (TJ) complex is a dynamic structure comprised of transmembrane claudins, occludin, and cytosolic proteins (ie, zonula occludens‐1, zonula occludens‐2, and zonula occludens‐3), which connect the TJ to the cytoskeleton . Expression of occludin and claudin‐1 is decreased in biopsy tissue of EoE patients both before and after treatment with swallowed corticosteroid .…”
Section: Introductionmentioning
confidence: 99%
“…2,5,7 The tight junction (TJ) complex is a dynamic structure comprised of transmembrane claudins, occludin, and cytosolic proteins (ie, zonula occludens-1, zonula occludens-2, and zonula occludens-3), which connect the TJ to the cytoskeleton. [8][9][10] Expression of occludin and claudin-1 is decreased in biopsy tissue of EoE patients both before and after treatment with swallowed corticosteroid. 2 In addition to tight junctions, multiple structural proteins contribute to the integrity and stratification of the esophageal epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Claudin-1 is a critical component of tight junctions and plays a crucial role in regulating proliferation and metastasis (Zeisel, Dhawan, Mingming Deng and Ye Zhang contributed equally to this work. & Baumert, 2018). Several studies have indicated that Claudin-1 is upregulated in colorectal (de Oliveira, de Oliveira, De Souza, & Morgado-Diaz, 2005), melanoma (Leotlela et al, 2007), and gastric cancer (Eftang et al, 2013) and can promote the epithelialmesenchymal transition (EMT; Stebbing, Filipović, & Giamas, 2013).…”
Section: Introductionmentioning
confidence: 99%